Toward Effective Learning: The Influence of Reflective Thinking and Academic Motivation on Self-Regulated Learning in Students - Zaharuddin Zaharuddin; Lukmawati Lukmawati; Siti Dini Fakhriya (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
Self-regulated learning is an important skill that enables undergraduate students to learn effectively, most student find it difficult to manage. Therefore, fostering reflective thinking and maintaining academic motivation are essential, as these two factors help students take better control of their own learning process. This study aims to examine the influence of reflective thinking and academic motivation on self-regulated learning among students of the Faculty of Psychology, Universitas Islam Negeri Raden Fatah Palembang. A quantitative approach was employed in this study. The sample consisted of 336 active students from the Faculty of Psychology, Universitas Islam Negeri Raden Fatah Palembang, selected using simple random sampling. Three instruments were used in this study. Reflective thinking was measured using the Reflective Thinking Questionnaire. Academic motivation was measured using the Academic Motivation Scale (AMS). Self-regulated learning was measured using an instrument based on the dimensions proposed by Pintrich.The results showed that reflective thinking and academic motivation significantly influenced self-regulated learning among students of the Faculty of Psychology, Universitas Islam Negeri Raden Fatah Palembang, with an effective contribution of 29.2%. Reflective thinking contributed 17.8% to self-regulated learning, while academic motivation contributed 11.4%. Higher education institutions can create activities and programs that encourage students to develop self-regulated learning skills, allowing students to take control of their learning processes and achieve their academic objectives through reflective thinking and increased academic motivation.